(3HgLI GdCdHGH aj Yde GdCSWQdGHs - (3YHO GdMdje Hf Shjde RGOg GdbjUQjs
(3ChdgG (B:s
(3GdMeO ddg QH GdCQHGH hHYO , adeG cGfJ GdBdGJ GdQUOjI eeG jMJGL Edjg , SjeG GdCSWQdGH dSeJ GdbHdI hGdChbGJ CQOJ Cf CcJH ajg QSGdI hSejJgG HHgLI GdCdHGH ai Yde GdCSWQdGH s
(3BNQgG (B:s
(3aCjgeG CcKQ EQJaGYkG agh GdCbQH Edjc , gPG EPG cGf bGJdgG GdCYdi eSGhjkG hcPG HdOjf (B( (3Ch (B) (3ehVYjf eQFjjf EPG cGfJ bGYOJgeG eJSGhjJjf hgPG GdbOQ caGjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3eQJHI Ydi ebOeI h(B18 (3HGHkG hNGJeIs
(3HChdgG Jedc eDQN SfI (B1282s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs